Perencanaan Strategik Usaha Kecil Menengah Jenis Usaha Kue dan Roti - Dianka Wahyuningtias (Binus Business Review, 2011)
Strategy is needed to sustainable business the year to come. This study is a descriptive case study using primary and secondary data which was collected from interviews, observations and literatures. Through a development strategy will be found various strategy which could be applicable by a company. The purpose of this research is to identify and evaluate the internal and external strategically factors of the company in UKM and to formulate several strategy alternatives applicable in developing UKM business develop program. Based on the TOWS matrix analysis, six alternatives strategies were produced, which includes having the own bakery shop, expanding partnership with bakeries in the jabodetabek area, implementing a differentiation products, increasing marketing activities, purposing bank loan, and investing on right equipment. After defining the conclusion, it is expected that UKM business, especially food industry, could use them to develop their business.